Studi Moderasi Beragama dalam Surat Al-Baqarah:126 dan Ali-Imran:159 serta Implikasinya pada PAI - Nuha Nafisah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to analyze the concept of religious moderation based on the perspective of Surah Al-Baqarah verse 126 and Surah Ali-Imran verse 159, as well as its implementation in Islamic Religious Education (PAI) in Indonesia. Using a qualitative approach with a library research method, the study collects data from tafsir books, scientific journals, academic articles, and previous research. The analysis shows that according to the interpretations of Ibn Kathir, Al-Qurthubi, and Al-Misbah, the values of religious moderation include love for the homeland, justice, gentleness, non-violence, and consultation. The implementation of these values in PAI is carried out theoretically through the integration of moderation values into the curriculum and practically through educators’ role modeling, habituation of values in the learning process, and supporting programs such as field studies and cultural festivals. Evaluation of this implementation is conducted through monitoring and instruments such as questionnaires and daily habit trackers. This study emphasizes the importance of religious education that not only focuses on cognitive aspects but also builds a moderate character within students. Thus, religious moderation can be sustainably instilled to shape an Indonesian society that is just, harmonious, and tolerant.